Refugee integration policies, gender issues & trauma - Figueiredo, Mariana Camelo (2019)
The recent influx of refugees has brought new adversities for countries which seek to grant asylum for displaced families. Policy makers and societies suddenly realize the challenges that urban systems face in integrating the sudden influx of newcomers. This dissertation provides an understanding of the role that states and societies play in the process of social integration of newcomers, using the context of Germany’s recent host of a large influx of refugee newcomers and subsequent integration policies mostly in the educational systems. This dissertation’s focal areas of study will be integration and refugee migrations as well as matters of gender and sexual orientation within the barriers of integration and the influence of trauma in performance and general well-being. I will provide context on the relevance in today’s political and social environment that understanding migration processes and what they bring to a society represents, I will contextualize as well the coming of mass migrations to Europe and the middle eastern conflicts that lead up to it. This research will include interviews with integration agents such as an education ministry member and professors and refugee students as well as community members which will allow me to reach meaningful conclusions towards policies and its real-life impacts. This dissertation brings together different data sources to describe the current characteristics of refugee integration; mostly in the educational system in Germany in the hope of informing future decision-making and policy formulation and provide awareness towards the importance and long-term range that integration measures carry.